2013
DOI: 10.18632/oncotarget.1619
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid enhancer binding factor-1 (LEF1) expression as a prognostic factor in adult acute promyelocytic leukemia

Abstract: Lymphoid enhancer-binding factor 1 (LEF1) is a downstream effector of the Wnt/ β-catenin signaling pathway. High LEF1 expression has been reported as a prognostic marker in hematologic malignancies. We evaluated the prognostic significance of LEF1 expression in 78 adult acute promyelocytic leukemia (APL) patients. APL samples were dichotomized at the median value and divided into: LEF1low and LEF1high. LEF1high patients had lower WBC counts at baseline and were less likely to carry a FLT3 -ITD than LEF1low pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…In present study we found that LEF1 low expression AML patients had higher WBC, BM blast percentages, lower platelets level, also had poor cytogenetic, and carried FLT-3 mutation. In agreement with our results, Metzeler et al, [14] conducted a study on 210 cytogenetically normal (CN)-AML patients, also by Albano et al [21]. Fu et al (2014) showed no signi cant di erence regarding age, WBC, FLT3-ITD mutations between LEF1 expression in 101 AML patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In present study we found that LEF1 low expression AML patients had higher WBC, BM blast percentages, lower platelets level, also had poor cytogenetic, and carried FLT-3 mutation. In agreement with our results, Metzeler et al, [14] conducted a study on 210 cytogenetically normal (CN)-AML patients, also by Albano et al [21]. Fu et al (2014) showed no signi cant di erence regarding age, WBC, FLT3-ITD mutations between LEF1 expression in 101 AML patients.…”
Section: Discussionsupporting
confidence: 92%
“…LEF1 high /low Gal.3 level patients had a signi cantly longer OS ( = 0.03, Figure 3) and borderline signi cantly better EFS ( = 0.05, Figure 3) than others (Table 5). level is a poor prognostic factor in myelodysplastic syndromes, AML [20], acute promyelocytic leukemia of adult patients [21], and childhood ALL [22]. In present study we found that LEF1 low expression AML patients had higher WBC, BM blast percentages, lower platelets level, also had poor cytogenetic, and carried FLT-3 mutation.…”
Section: Discussionsupporting
confidence: 55%
“…It also mediates Wnt signaling-induced proliferation increase of pro B cells. LEF1 expression is reported to be involved in leukemic transformation [ 4 ], and associated with poor prognosis in adult B precursor acute lymphoblastic leukemia (ALL) [ 6 ], chronic lymphocytic leukemia(CLL)[ 6 , 7 ], cytogenetically normal acute myeloid leukemia (AML), and adult de novo acute promyelocytic leukemia (APL)[ 8 ]. These reports indicate that LEF1 is involved in the oncogenesis of leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study suggests a possible link between the degree of LEF1 overexpression and poor prognosis in adult B‐precursor ALL and chronic lymphocytic leukemia . However, a more recent study showed that high LEF1 level is a favorable prognostic factor in cytogenetically normal acute myeloid leukemia (CN‐AML) , AML , and acute promyelocytic leukemia (APL) of adult patients. Here, our study reports that high LEF1 expression is associated with favorable CR rate and OS in childhood ALL.…”
Section: Discussionmentioning
confidence: 99%